2013
DOI: 10.1038/modpathol.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Expression microarray analysis identifies novel epithelial-derived protein markers in eosinophilic esophagitis

Abstract: Gene expression studies in eosinophilic esophagitis support an immune-mediated etiology associated with differential regulation of inflammatory and epithelial-derived genes. We aimed to further characterize epithelial gene expression alterations in eosinophilic esophagitis and to explore the use of immunohistochemistry to identify these alterations. Esophageal biopsies from pediatric patients with eosinophilic esophagitis before and after therapy with topical steroids (N ¼ 7) were screened by gene expression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
2
40
1
1
Order By: Relevance
“…Previous studies of EoE have identified sets of genes (~500) whose esophageal expression can discriminate EoE from non-EoE. (6, 10, 32, 33) This work led to the development of a smaller set of genes that provides strong discriminatory value (the EDP) for individuals who have ≥ 15 eosinophils/hpf in the esophagus compared to those with ≤2 eosinophils/hpf in the esophagus. (11) Thus, the PEESS ® v2.0 dysphagia domain captures information associated with alterations in esophageal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of EoE have identified sets of genes (~500) whose esophageal expression can discriminate EoE from non-EoE. (6, 10, 32, 33) This work led to the development of a smaller set of genes that provides strong discriminatory value (the EDP) for individuals who have ≥ 15 eosinophils/hpf in the esophagus compared to those with ≤2 eosinophils/hpf in the esophagus. (11) Thus, the PEESS ® v2.0 dysphagia domain captures information associated with alterations in esophageal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, 6.1 % of patients with EoE had a FLG loss-of-function mutation versus only 1.3 % of normal controls ( p = .0172) [ 21 ]. A more recent study on a cohort of 47 EoE patients found that fi laggrin was greatly underexpressed compared to controls [ 22 ]. Specifi cally, fi laggrin expression was positive in 88 % of controls, in 100 % of GERD patients, and in 0 % of patients with EoE ( p < .001) [ 22 ].…”
Section: Filaggrin and Eosinophilic Esophagitismentioning
confidence: 90%
“…A more recent study on a cohort of 47 EoE patients found that fi laggrin was greatly underexpressed compared to controls [ 22 ]. Specifi cally, fi laggrin expression was positive in 88 % of controls, in 100 % of GERD patients, and in 0 % of patients with EoE ( p < .001) [ 22 ]. While FLG mutation likely does not explain the entire disease process of EoE, it shows how GI pathology is indeed linked to this barrier protein and its dysfunction.…”
Section: Filaggrin and Eosinophilic Esophagitismentioning
confidence: 96%
“…A recent twin study revealed that if a sibling has EoE, there exists a risk of 2.4% of subsequent children developing EoE. 7 A variety of EoE genes provide clues to dysfunction of the epithelial barrier (filaggrin), 8 immune system (thymic stromal lymphopoietin, eotaxin-3) 9,10 11 and other yet to be identified areas (calpain-14). 12,13 …”
Section: Eosinophilic Gastrointestinal Diseasesmentioning
confidence: 99%